Performance of Laying Chickens with Feed Additive Cinnamon Flour (Cinnamomum burmanni (Nees & T.Nees) Blume) - Florencia Sompie; Jein Riny Leke; Jacqueline Laihad; Hengky Kiroh; Nontje Kumajas; Ratna Siahaan (JURNAL BIOS LOGOS, 2024)
Chickens are important commodities due to human need eggs to meet animal protein. Increasing of resistance of bacteria to synthetic antibiotics and consumer understanding of health and food safety have stimulated use of antibiotic growth promoters (AGP) in poultry industry. AGP applied sustainable feed management steps to improve gut health and poultry growth performance. Cinnamon, one of the spices as a natural product. This useful source due to antioxidants, anti-microbial, anti-inflammatory, antifungal, and hypo-cholesterolemic effects and its capability to activate digestion enzymes in intestine. This research aimed to analyze the performance of laying chicken eggs fed with cinnamon flour. The treatments used were cinnamon flour with levels R0 (basal ration, without cinnamon flour/CF, R1 (99.5% BR+ 0.5% CF), R2 (99% BR+ 1% CF), R3 (98% BR + 1.5 % CF), and R4 (98% BR + 2% CF). Data were analyzed with Completely Randomized Design and Duncan's test. Variables were ration consumption, Hen Day Production/HDP and ration conversion. Results showed that adding 2% cinnamon flour significant effect on feed consumption, HDP (P< 0,01) but insignificant on ration conversion (P>0.05). Cinnamon flour as feed additive source up to 2% level can increase the performance of laying hens.